2011
DOI: 10.1186/1475-2891-10-80
|View full text |Cite
|
Sign up to set email alerts
|

The role of soluble fiber intake in patients under highly effective lipid-lowering therapy

Abstract: BackgroundIt has been demonstrated that statins can increase intestinal sterol absorption. Augments in phytosterolemia seems related to cardiovascular disease.ObjectiveWe examined the role of soluble fiber intake in endogenous cholesterol synthesis and in sterol absorption among subjects under highly effective lipid-lowering therapy.DesignIn an open label, randomized, parallel-design study with blinded endpoints, subjects with primary hypercholesterolemia (n = 116) were assigned to receive during 12 weeks, a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 35 publications
0
16
0
2
Order By: Relevance
“…Beta glucan (β‐glucan) is a soluble fiber readily available from oat and barley grains that has been gaining interest due to its multiple functional and bioactive properties. Several randomized controlled trials revealed anti obesity effect of dietary fiber .…”
Section: Primers and Protocol Details For Pcrmentioning
confidence: 99%
“…Beta glucan (β‐glucan) is a soluble fiber readily available from oat and barley grains that has been gaining interest due to its multiple functional and bioactive properties. Several randomized controlled trials revealed anti obesity effect of dietary fiber .…”
Section: Primers and Protocol Details For Pcrmentioning
confidence: 99%
“…Several studies show that soluble fiber supplements can contribute to weight loss, primarily by increasing feelings of fullness and reducing appetite. [23] It looks like RS has the same effect. Adding RS to meals increases feelings of fullness and makes people eat fewer calories.…”
Section: Benefits Against Health and Disease Fightingmentioning
confidence: 83%
“…According to Handayani et al (2017), this jelly was known as healthy food or drink because it contained high concentration of soluble fiber and lowcalorie. High soluble fiber had been proven to reduce lipid profiles (Ramos et al 2011;Wahyono et al 2015;Handayani et al 2017). The Indonesian Ministry of Health's Nutrition Directorate (year of 1992) stated that 100 grams of black jelly contained 6.23 grams of crude fiber.…”
Section: Introductionmentioning
confidence: 99%